Financial Friction, Domestic Credit and Income Inequality in Emerging Economies: Comparative IV-GMM and Threshold Analyses from Nigeria and South Africa - Adeleye, Bosede Ngozi; Osabuohien, Evans; Adam, Lukman Shehu (Asian Economic and Financial Review, 2022)
This study comparatively investigates the intrinsic nexus of financial friction (proxied by interest rate spread), domestic credit and income inequality in emerging economies using quarterly time series data on Nigeria and South Africa from 1980 to 2015. It also investigates whether interest spread and domestic credit independently reduce inequality and if inequality responds to domestic credit and interest spread when interest spread is below or above its threshold. Findings revealed that (1) domestic credit aggravates inequality in both countries; (2) the impact of interest spread is asymmetric; (3) interest spread reduces the devastating effect of credit on inequality; and (4) the behavior of inequality with respect to domestic credit and interest spread is mixed given the interest spread threshold. Based on the results, a policy mix approach should be pursued since credit and financial friction exert a heterogeneous impact.